Strategi Komunikasi Kepala Sekolah: Implementasi Teknik Umpan Balik Berbasis Digital di Era Pendidikan 4.0. - Azizah Putriana; Welma Daswita; Gusmaneli Gusmaneli (Jurnal Ilmiah Literasi Indonesia, 2026)
The Education 4.0 era demands a comprehensive transformation in the education system, including communication patterns in school leadership. This study aims to analyze the communication strategies of school principals through the implementation of digital-based feedback techniques to improve management efficiency and the quality of learning. The method used is a qualitative approach with a literature study and document analysis related to technology integration in schools. The results of the study indicate that the use of digital platforms (such as Learning Management Systems and communication applications) enables school principals to provide timely, measurable, and effective feedback to both teachers and students. Effective communication strategies involve strengthening a digital vision, developing technological literacy competencies among educators, and fostering a collaborative culture of innovation. However, challenges such as limited infrastructure and gaps in digital literacy remain major obstacles in its implementation. This study concludes that strong digital leadership through technology-based feedback mechanisms is crucial to ensure sustainable, adaptive, and transparent educational administration in the Industry 4.0 era.